Rancang Bangun Sistem Pendukung Keputusan Rekomendasi Agent Terbaik Dengan Metode SAW - Augie, Peter; Yulistia, Yulistia (Jurnal Teknologi Sistem Informasi, 2022)
Insurance at PT MAG is a general insurance company under the auspices of PT Asuransi Multi Artha Guna (Tbk). To sell insurance premiums, of course, companies need agents to increase sales. The company's goal is of course to find out which agent has the greatest impact in the form of the highest sales for the company. However, because the agents who work in PT MAG have a lot of sales data and performance data, it is difficult for the company to recommend the best agent. A Decision Support System for the Selection of the Best agents will be developed. This system was developed using the Rational Unified Process (RUP) methodology, usecase diagrams, Class Diagrams, Activity Diagrams, entity relationship diagrams, PHP programming language with Laravel Framework. The results and conclusions of creating this Decision Support System can help companies in making decisions in the recommendations of the best agent more easily and providing transparent information to employees brief.